The ideological divide and climate change opinion: “top-down” and “bottom-up” approaches - Jacquet, Jennifer; Dietrich, Monica; Jost, John T. (Frontiers in Psychology, 2014)
The United States wields disproportionate global influence in terms of carbon dioxide emissions and international climate policy. This renders it an especially important context in which to examine the interplay among social, psychological, and political factors in shaping attitudes and behaviors about climate change. In this article, we review the emerging literature addressing the liberal-conservative divide in the U.S. with respect to thought, communication, and action concerning climate change. Because of its theoretical and practical significance, we focus on the motivational basis for skepticism and inaction on the part of some, including “top-down” institutional forces, such as corporate strategy, and “bottom-up” psychological factors, such as ego, group, and system justification. Although more research is needed to elucidate fully the social, cognitive, and motivational bases of environmental attitudes and behavior, a great deal has been learned in just a few years by focusing on specific ideological factors in addition to general psychological principles.